Employment and performance effects of circular economy innovations - Jens Horbach; Christian Rammer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Circular economy (CE) describes an economic concept that aims at saving resources by minimizing the use of material and energy over the entire life-cycle or products, including repair, reuse and recycling. CE innovations help to realize the goals of a sustainable development and target both the environmental, economic and social dimensions of sustainability. This paper looks at the economic and social dimensions by investigating the performance and employment effects of CE innovations at the firm level. CE innovations such as the reduction of energy and material consumption or the recycling of waste, water or material may lead to cost savings which in turn can increase the competitiveness of the firm and raise demand for a firm's products. Our econometric analysis uses data of two waves of the German part of the Community Innovation Survey (CIS). The performance effects of CE innovations measured by the financial standing of a firm and by turnover growth tend to be positive. The results of quantile regressions show that this is also the case for employment effects.
Keywords: C21; Q01; Q55; 330; circular economy; Community Innovation Survey; eco-innovation; quantile regression